Bullying Behavior Among Elementary School Students In East Bandung Region - Chodijah, Medina (Universitas Muhammadiyah Surakarta, 2018)
Bullying behavior among school students known as school bullying is rapidly increasing. Generally, children who are victims of bullying will feel unhappiness, especially when they are in an environment where they are being bullied. This study aims to obtain factual data about the bullying behavior at elementary school children located in East Bandung area. This is a descriptive research with quantitative approach. The number of sample used in this study was 494 children aged between 10-12 years who attend elementary school in East Bandung area. The instruments used in this study are a modified questionnaire from The Children's Happiness Scale and the Illinois Bully Scale. The data obtained then presented in the form of tables and graphs. The results showed that students had been victims of bullying and/or had done bullying in various types and levels. In general, verbal psychological bullying forms are ranked top for both boys and girls, followed by non-verbal psychological bullying and the last is physical bullying.